Medicinal plants and natural compounds against acyclovir-resistant HSV infections - Xu, Lin; Zhong, Xuan-Lei; Xi, Zhi-Chao; Li, Yang; Xu, Hong-Xi (Frontiers in Microbiology, 2022)
Herpes simplex virus (HSV), an alphaherpesvirus, is highly prevalent in the human population and is known to cause oral and genital herpes and various complications. Represented by acyclovir (ACV), nucleoside analogs have been the main clinical treatment against HSV infection thus far. However, due to prolonged and excessive use, HSV has developed ACV-resistant strains. Therefore, effective treatment against ACV-resistant HSV strains is urgently needed. In this review, we summarized the plant extracts and natural compounds that inhibited ACV-resistant HSV infection and their mechanism of action.